2024
DOI: 10.1039/d3en00747b
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic nanosized metal–organic framework composites for the targeted removal of hydrophobic pharmaceuticals with outstanding bacterial anti-adhesion properties

Subhrajyoti Ghosh,
Abhijeet Rana,
Anjali Patel
et al.

Abstract: The increasing concentration of pharmaceutical waste in environmental water bodies after the COVID-19 pandemic has accelerated the urgency of removing various drugs from wastewater specimens. Realizing this concern, herein, for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…2a and b). 29 The vacant linker defect sites are occupied by six trifluoroacetate (modulator) anions for each Zr 6 cluster, which was proved by EDX (Fig. S4†) and 19 F NMR (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…2a and b). 29 The vacant linker defect sites are occupied by six trifluoroacetate (modulator) anions for each Zr 6 cluster, which was proved by EDX (Fig. S4†) and 19 F NMR (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…To quantify these missing linker defects in 1′ , we employed methodologies from reported literature. 29 It was calculated that the molecular weight of an ideal, dehydroxylated, solvent-free hexanuclear Zr 6 cluster was determined to be 4.4 times higher than that of six ZrO 2 unit. Calculations based on TGA (given in the ESI†) showed that the experimental plateau ( W Exp.…”
Section: Resultsmentioning
confidence: 99%
“…This newly developed adsorbent exhibited high adsorption capacity, even higher than the adsorption capacity reported in our previous work. 17 The previous fluorinated adsorbent from our group has an adsorption capacity of 86.5 and 148.0 mg/g for favipiravir and diflunisal, respectively. Meanwhile, for SHMOF′, the adsorption capacity for flurbiprofen drug and fluazinam pesticide is 435.3 and 575.6 mg/g, respectively.…”
Section: ■ Introductionmentioning
confidence: 93%
“…We designed a fluorinated MOF to gain hydrophobicity and used the hydrophobic nature of that adsorbent to remove the hydrophobic drugs (favipiravir and diflunisal), but it has poor adsorption capacity. 17 To address the above-mentioned issue, we fabricated an ultrarobust, environmentally friendly MOF-based adsorbent (SHMOF′) with a long-chain hydrocarbon functionalization to gain hydrophobicity. As previously mentioned, numerous adsorbents are accessible for isolating hydrophilic drugs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation